2018
DOI: 10.1136/bmj.k497
|View full text |Cite
|
Sign up to set email alerts
|

Age trends in 30 day hospital readmissions: US national retrospective analysis

Abstract: ObjectiveTo assess trends in and risk factors for readmission to hospital across the age continuum.DesignRetrospective analysis.Setting and participants31 729 762 index hospital admissions for all conditions in 2013 from the US Agency for Healthcare Research and Quality Nationwide Readmissions Database.Main outcome measure30 day, all cause, unplanned hospital readmissions. Odds of readmission were compared by patients’ age in one year epochs with logistic regression, accounting for sex, payer, length of stay, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
67
5
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(84 citation statements)
references
References 55 publications
9
67
5
3
Order By: Relevance
“…The general patterns in the prevalence of SUDs and chronic conditions are consistent with prior studies (Gerteisetal.,2014; Ward and Schiller, 2013; Wu et al, 2015). The associations between SUDs and hospitalization by chronic condition status are in line with other studies of hospitalizations (Berry et al, 2018; Jiang et al, 2015). …”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The general patterns in the prevalence of SUDs and chronic conditions are consistent with prior studies (Gerteisetal.,2014; Ward and Schiller, 2013; Wu et al, 2015). The associations between SUDs and hospitalization by chronic condition status are in line with other studies of hospitalizations (Berry et al, 2018; Jiang et al, 2015). …”
Section: Discussionsupporting
confidence: 88%
“…Males and African American/Black patients (versus Caucasians/Whites) had elevated odds of tobacco, alcohol, and any drug use disorder. The results call for developing infrastructure support and training for primary care providers to assess and treat comorbid alcohol/drug use disorders and chronic conditions, especially among males, African American/Black patients, and adults with multiple chronic diseases (Berry et al, 2018; Hayes et al, 2016). …”
Section: Discussionmentioning
confidence: 99%
“…A recent study on 30-day hospital readmissions using Agency for Healthcare Research and Quality Nationwide Readmissions Database demonstrated that the presence of multiple chronic conditions had the highest odds of hospital readmission (for example, 3.67 (3.64 to 3.69) for six or more versus no chronic conditions). 29 This study also determined that mental health is one of the most common reasons for index admissions that had high adjusted readmission rates (≥75th percentile). Furthermore, readmission rates vary significantly by type of insurance (private 7.0%, Medicaid 10.1%, and Medicare 16.4%).…”
Section: Discussionmentioning
confidence: 98%
“…These factors are less relevant in patients undergoing appendectomy. 66 There is wide variation in the rate of readmission postappendectomy among the included papers. This meta-analysis identified factors increasing these rates of readmission, such as complicated appendicitis, diabetes and open approach to surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Berry and colleagues recently suggested in a retrospective analysis of over 31 million index hospital admission that readmission was associated with age between 16 and 20 years of age, associated chronic conditions, and mental health issues. These factors are less relevant in patients undergoing appendectomy …”
Section: Discussionmentioning
confidence: 99%